Green fabrication of biologically active magnetic core-shell Fe3O4/Au nanoparticles and their potential anticancer effect - Izadiyan, Zara; Shameli, Kamyar; Miyake, Mikio; Teow, Sin Yeang *; Peh, Suat Cheng *; Shaza Eva M,; Siti Husnaa, M T (Elsevier, 2019)
Core-shell Fe3O4/Au nanostructures were constructed using an advanced method of two-step synthesis from Juglans regia (walnut) green husk extract. Several complementary methods were applied to investigate structural and magnetic properties of the samples. X-ray diffraction (XRD), high-resolution transmission electron microscopy (HR-TEM), electron diffraction, optical, thermogravimetric analysis (TGA), and vibrating sample magnetometer (VSM) were used for nanoparticle characterizations. As shown by HR-TEM, the mean diameter of core-shell Fe3O4/Au nanoparticles synthesized using co-precipitation method was 6.08 ± 1.06 nm. This study shows that the physical and structural properties of core-shell Fe3O4/Au nanoparticles possess intrinsic properties of gold and magnetite. VSM revealed that the core-shell Fe3O4/Au have high saturation magnetization and low coercivity due to the magnetic properties. The core-shell nanoparticles show the inhibitory concentration (IC)50 of 235 μg/ml against a colorectal cancer cell line, HT-29. When tested against non-cancer cells, IC50 was not achieved even up to 500 μg/ml. This study highlights the magnetic properties and anticancer action of core-shell Fe3O4/Au nanoparticles. This compound can be ideal candidate for cancer treatment and other biomedical applications.